Advancing Sustainability and Social Justice: Developing Sustainability Societies for Muslim Women - Datta, Rimmi; Mete, Jayanta (Religion and Policy Journal, 2024)
Research Problem: Muslim women in developing countries face unique challenges influenced by cultural, religious, and socioeconomic factors. These challenges impact their ability to participate in sustainable development initiatives, despite Islamic teachings emphasizing environmental stewardship, social justice, and equitable economic opportunities. Research Purposes: This paper explores the concept of "Sustainability Societies" tailored for Muslim women, integrating Islamic values with principles of environmental sustainability, social justice, and economic development. The study aims to demonstrate how empowering Muslim women can contribute to achieving global sustainability goals while promoting communal well-being and economic resilience. Research Methods: The research adopts a systematic and theoretically grounded approach, synthesizing Islamic moral teachings, empirical data, and sustainability frameworks. It evaluates the feasibility of intervention programs that empower Muslim women to lead sustainable enterprises and contribute to social and environmental change. Results and Discussion: Findings indicate that creating sustainability societies for Muslim women can significantly enhance social inclusion, environmental protection, and economic empowerment. These societies provide a practical model for addressing unsustainable practices, fostering leadership roles for women, and aligning sustainability goals with Islamic values. The research highlights the importance of culturally appropriate programs that integrate local traditions and global sustainability standards. Research Implications and Contributions: The study offers actionable recommendations for policymakers, educators, and community leaders to design effective and inclusive programs for Muslim women. These initiatives can address global environmental challenges, strengthen community resilience, and mobilize women as agents of sustainable change. The paper emphasizes the potential of these strategies to contribute to sustainability targets while preserving Islamic moral values and social justice.